Unveiling the post-pandemic hybrid education: Students' and professors' perspectives on the contingent virtual education modality (Revista Electrónica Calidad en la Educación Superior, 2023)
This study used a mixed parallel-convergent typology design to assess the impact of “pandemic pedagogies” on professors and students. Online surveys and in-depth interviews Survey findings showed that most educators reported medium to high competence in technology, organizational and student management, alongside stressors related to virtual education's impact on their quality of life. Similarly, students experienced physical fatigue, boredom, exhaustion, and passivity. Interviews revealed educators' aspirations to address these challenges, secure enhanced administrative support, and strengthen pedagogical management. Pandemic pedagogies revealed learning challenges and opportunities for transformative changes in nursing education across all levels.